‘Jews to Madagascar’: Poland in the face of ethnical problems in the 1930s - Trębacz, Zofia (European Spatial Research and Policy, 2021)
The idea of deporting the Jewish population of Europe was part of a modern anti-Semitism. Poland was no exception in this regard. Under the influence of other countries implementing anti-Jewish laws, also Polish anti-Semitism became more radical. After 1935, such postulates were openly expressed as the policy of the Polish government has changed its character – from state to national. Additionally, due to the global economic crisis the idea began to be taken far more seriously not just in national Catholic circles. The resettlement of Jews was seen as the way to reduce unemployment and to ‘Polonise’ Polish cities, as masses of poor peasants could replaced the Jewish workers as far as trade and craftsmanship were concerned. The authors of immigration plans for European Jews suggested evacuating them most willingly to uncivilised countries – including Madagascar (a French colony) – due to the fact that their lands were either not used at all or only used to an insufficient and inadequate extent. In Poland, the idea was first adopted in 1926 as a solution to the problem of overpopulation in rural areas. However, the conditions on the island did not allow settlement and soon the idea fell through. Yet it came back a decade later as a proposal of deporting exclusively Polish Jews. At the time, the project was taken much more seriously and in 1937 the Polish government commissioned a task force to examine the possibility of settling in Madagascar and to evaluate the island’s potential, in particular its climate and labour conditions. But the reports of the commission members were full of contradictions and the French were showing growing caution on the matter.